Health-Related Quality of Life and Its Associated Predictors in Patients with Oral Lichen Planus: A Cross-Sectional Study - Paswach Wiriyakijja; Stephen Porter; Stefano Fedele; Tim Hodgson; Roddy McMillan; Martina Shephard; Richeal Ni Riordain (Elsevier, 2021)
Objectives: To investigate levels of quality of life (QoL) and determine associated predictors in patients with oral lichen planus (OLP). Materials and methods: A total of 300 patients with OLP at one tertiary Oral Medicine clinic in the UK were recruited in a cross-sectional study from January 2018 to July 2019. The 15-item Chronic Oral Mucosal Disease Questionnaire (COMDQ-15) and 14-item Oral Health Impact Profile (OHIP-14) were used to assess the level of QoL related to OLP. A number of potential determinants were considered, including patient demographics, treatment, the severity of oral symptoms, the clinical activity of the disease, and the patient psychological status, which were measured using the pain-Numerical Rating Scale, the Oral Disease Severity Score, the Hospital Anxiety and Depression Scale, and the 10-item Perceived Stress Scale. Multivariate linear regression was employed to identify independent determinants associated with overall and aspects of QoL. Results: On multivariate analyses, after adjusting for confounding variables, the QoL levels in patients with OLP were significantly associated with levels of oral pain, anxiety, stress and use of topical corticosteroids. The COMDQ-15 instrument performed better than OHIP-14 at capturing the association between QoL and pain and disease activity in patients with OLP. Conclusion: Clinicians should expect reduced QoL in OLP patients with high pain levels, high anxiety levels, high perceived stress and use of topical corticosteroids. The COMDQ-15 is best suited to measure QoL in this population.